Macrophage Gene Expression in Adipose Tissue is Associated with Insulin Sensitivity and Serum Lipid Levels Independent of Obesity. (13th June 2013) - Ahlin, S.; Sjöholm, K.; Jacobson, P.; Andersson‐Assarsson, J.C.; Walley, A.; Tordjman, J.; Poitou, C.; Prifti, E.; Jansson, P.‐A.; Borén, J.; Sjöström, L.; Froguel, P.; et al.
<x xml:space="preserve">Abstract</x> Objective: Obesity is linked to both increased metabolic disturbances and increased adipose tissue macrophage infiltration. However, whether macrophage infiltration directly influences human metabolism is unclear. The aim of this study was to investigate if there are obesity‐independent links between adipose tissue macrophages and metabolic disturbances. Design and Methods: Expression of macrophage markers in adipose tissue was analyzed by DNA microarrays in the SOS Sib Pair study and in patients with type 2 diabetes and a BMI‐matched healthy control group. Results: The expression of macrophage markers in adipose tissue was increased in obesity and associated with several metabolic and anthropometric measurements. After adjustment for BMI, the expression remained associated with insulin sensitivity, serum levels of insulin, C‐peptide, high density lipoprotein cholesterol (HDL‐cholesterol) and triglycerides. In addition, the expression of most macrophage markers was significantly increased in patients with type 2 diabetes compared to the control group. Conclusion: Our study shows that infiltration of macrophages in human adipose tissue, estimated by the expression of macrophage markers, is increased in subjects with obesity and diabetes and associated with insulin sensitivity and serum lipid levels independent of BMI. This indicates that adipose tissue macrophages may contribute to the development of insulin resistance and dyslipidemia.